2018
DOI: 10.1002/anie.201808453
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Driven Keto–Enol Tautomerization: Atomistic Insights into Enol Formation and Stabilization Mechanisms

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(98 citation statements)
references
References 26 publications
(13 reference statements)
10
86
0
2
Order By: Relevance
“…Schauermann et al. reported the synthesis of the enol of acetophenone on metal surfaces stabilized by intermolecular interactions with the keto form of a second molecule to give a ketone‐enol dimer . Turecek et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schauermann et al. reported the synthesis of the enol of acetophenone on metal surfaces stabilized by intermolecular interactions with the keto form of a second molecule to give a ketone‐enol dimer . Turecek et al .…”
Section: Methodsmentioning
confidence: 99%
“…[29] Schauermann et al reported the synthesis of the enol of acetophenone on metal surfaces stabilized by intermolecular interactions with the keto form of a second molecule to give a ketone-enol dimer. [34] Turecek et al [26] generated the enol of g-butyrolactone in the gas phase and characterized it by neutralization-reionization mass spectrometry. They found that the lactone enol persists as an isolated molecule in the gas phase.…”
mentioning
confidence: 99%
“…beschrieben die Darstellung des Enols von Acetophenon auf Metalloberflächen. Das Enol wird hierbei durch eine intermolekulare Wechselwirkung mit einem zweiten Molekül Acetophenon in Form eines Keto‐Enol Dimers stabilisiert . Turecek et al .…”
Section: Methodsunclassified
“…Das Enol wird hierbei durch eine intermolekulare Wechselwirkung mit einem zweiten Molekül Acetophenon in Form eines Keto-Enol Dimers stabilisiert. [34] Turecek et al [26] konnten das Enol von g-Butyrolacton in der Gasphase darstellen und Enole kçnnten ebenfalls eine Rolle in der Chemie des interstellaren Mediums spielen. Diese Hypothese wird durch die Entdeckung von Ethenol (5) im Jahr 2001 in Sagittarius B2 anhand von Mikrowellenemissionen bekräftigt.…”
unclassified
“…2−4 One obvious reason is the influence of the surface on each single adsorbed molecule, steric or electronic or by strong local electric fields, 5 leading to intramolecular changes, as for example, in surface-driven ketoenol tautomerization. 6 However, intermolecular interactions between several surface-adsorbed molecules are also clearly important, as demonstrated by ligand-directed heterogeneous catalysis. 7,8 Hence, molecular interaction and self-assembly on (metal) surfaces 9−11 is not only a research field on its own, ranging from investigations of interaction modes 12,13 to two-dimensional crystal engineering 14 but also an important ingredient for onsurface synthesis and heterogeneous catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%